PERAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Putri, Nur Amelia; Nukman, Muhamad (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2024)
The Merdeka Curriculum demands a significant and comprehensive role for teachers, starting from planners, designers, managers, evaluators, researchers, decision makers, to learning administrators. The aim of this research is to describe in detail the conditions related to the role of teachers in implementing the Independent Curriculum at SDN 017 Mayang Pongkai. The method used in this research is a qualitative approach with case studies. Researchers used various data collection techniques, such as observation, interviews and document analysis, involving research subjects, namely the class V homeroom teacher at SDN 017 Mayang Pongkai. Based on the research results, it can be concluded that the independent curriculum has been implemented well according to its role. The role of teachers in implementing the Independent Curriculum includes teacher, educator, facilitator, guide, servant, designer, manager, innovator and assesor.